Inter-confessional Relations and (In)tolerance among the Vlachs (16th-17th Centuries) - Šarić, Marko (Array, 2007)
Author gave an extended description of inter-confessioal relationships within the world of the Dinaric Morlachs. The fragmentation of Morlach societies between the border and transhumant areas determined multiplied differences, toleration and intolerance.